Righteous - Ahdieh, Renee (New York G. P. Putnam's Sons, 2021)
"After Celine disappears, Pippa's resolve to find her takes her into the dangerous world of the fey"--
Ages 12+.
Grades 7-9.
112784
Keywords: 1800-1899; Fairies -- Juvenile fiction; Vampires -- Juvenile fiction; Weddings -- Juvenile fiction; Love -- Juvenile fiction; French -- Louisiana -- New Orleans -- Juvenile fiction; Young adult fiction; Supernatural -- Fiction; Love -- Fiction; Young Adult Fiction -- Romance -- Paranormal; Young Adult Fiction -- Fantasy -- Epic; Young Adult Fiction -- Vampires; Occult fiction; Love stories; New Orleans (La.) -- History -- 19th century -- Juvenile fiction; Young adult fiction; Fictional Work; Young adult works; Juvenile works; History; Fiction; Novels; Paranormal fiction; Romans